Granulocyte transfusions in children and adults with hematological malignancies: benefits and controversies. Issue 1 (December 2015) - Cugno, Chiara; Deola, Sara; Filippini, Perla; Stroncek, David; Rutella, Sergio
Abstract Bacterial and fungal infections continue to pose a major clinical challenge in patients with prolonged severe neutropenia after chemotherapy or hematopoietic stem cell transplantation (HSCT). With the advent of granulocyte colony-stimulating factor (G-CSF) to mobilize neutrophils in healthy donors, granulocyte transfusions have been broadly used to prevent and/or treat life-threatening infections in patients with severe febrile neutropenia and/or neutrophil dysfunction. Although the results of randomized controlled trials are inconclusive, there are suggestions from pilot and retrospective studies that granulocyte transfusions may benefit selected categories of patients. We will critically appraise the evidence related to the use of therapeutic granulocyte transfusions in children and adults, highlighting current controversies in the field and discussing complementary approaches to modulate phagocyte function in the host.